Two Rationally Identified Novel Glitazones Reversed the Behavioral Dysfunctions and Exhibited Neuroprotection Through Ameliorating Brain Cytokines and Oxy-Radicals in ICV-LPS Neuroinflammatory Rat Model - Justin, Antony; Ashwini, Premkumar; Jose, Jincy A.; Jeyarani, Victoria; Dhanabal, S. P.; Manisha, Chennu; Mandal, Subhankar P.; Bhavimani, Guru; Prabitha, P.; Yuvaraj, S.; Prashantha Kumar, B. R. (Frontiers in Neuroscience, 2020)
The present study has planned to evaluate the neuroprotective activity of two novel glitazones in neuroinflammatory rat model. Two novel glitazones were selected from in house virtual library of glitazones based on their docking scores against PPAR-γ protein and other parameters studied in in sillico computational studies. Initially, acute oral toxicity study was carried out for glitazones in rats to assess the toxicity profile and to determine the therapeutic range for the neuroprotective evaluation. Prior to induction of neuroinflammation, the treatments with glitazones (G1 & G2) and standard Pioglitazone were made for consecutive four days to respective groups. On the fifth day, the neuroinflammation was induced by intracerebroventricular (ICV) administration of Lipopolysaccharides (LPS) (2µg/µl) using stereotaxic apparatus. After 7 days, the rats were subjected to behavioral assessment followed by neurobiochemicals evaluation and histopathological studies. The pre-treatment with glitazones at two dose levels (15 & 30 mg/kg) have significantly reversed the behavioral dysfunctions. Glitazones have shown significant reduction in the levels of LPO, NO, TNF-α, IL-1β and also increased the levels of anti-oxidant enzymes such as SOD, CAT and GSH in the brain of LPS administered rats. The neuroprotection exhibited by two novel glitazones is comparable with standard pioglitazone. The PPAR-γ dependent amelioration of cytokines and oxy-radicals release by novel glitazones during neuroinflammatory conditions may be attributed for the reversal of behavioral dysfunctions through preventing the degeneration of neurons in major regions of brain.